Islamic Economic Ethics and Relevance in Era Global Capitalism : Study of Interpretation Verses of Commerce - Nurfadilah, Aninda; Syafaat, Aris; Harahap, Kholik Fazrin; Nofriansah, Amat Oky; Hakim , Lukmanul; Arni, Jani (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
Analyze the relevance of Islamic economic ethics in the practice of buying and selling in the era of global capitalism, focusing on the study of the interpretation of verses related to buying and selling transactions in the Qur'an. This study uses a normative interpretation approach and contemporary analysis of verses that talk about buying and selling, in surah Al-Baqoroh 198, Al-Baqarah verse 275, Al-Baqoroh 282 and An-Nisa 29. In addition, this study also assesses how the principles of Islamic economics can be applied in the context of modern capitalism which often prioritizes maximum profit and individualism. The results of the study show that Islamic economic ethics that prioritize justice, transparency, and social balance are still very relevant to be applied in the current global economic system. Principles such as the prohibition of usury, gharar (uncertainty), and tyranny in buying and selling can be the basis for transactions that are fairer and do not harm certain parties. The conclusion of this study is that the application of Islamic economic ethics in the practice of buying and selling can provide alternative solutions to overcome economic inequality caused by global capitalism, as well as support the creation of more equitable and sustainable welfare for society as a whole.